Diet as a risk factors of prostate cancer: a literature review - Norzaher Ismail; Shamsul Azhar Shah; Nazarudin Safian; Syafiq Taib; Siti Nor Mat (Penerbit Universiti Kebangsaan Malaysia, 2019)
Introduction Prostate cancer is indeed a raising health problem in the world. As our life expectancy improves, the prevalence of prostate cancer may also increase. Diet is believed to be one of the common major risk factors contributing to the development of prostate cancer. Objective This review aims to i) understand the effect of dietary habit towards risk of developing prostate cancer, ii) to summarize the published articles on risk of developing prostate cancer and iii) to provide information in designing the optimal diet for primary and secondary prostate cancer prevention. Methods A search was conducted to review published studies on prostate cancer and diet through PubMed/MEDLINE, Google Scholar and Science Direct. Results High intake of red meat, processed meat and dairy products were commonly linked to the prostate cancer while consumption of antioxidants and certain vitamins may give protective mechanism towards prostate cancer. Conclusions Diet of low carbohydrates, n-3 PUFAs, colorful fruits and vegetables are still the best advice to counsel the patient while lifestyle of smoking and heavy alcohol intake should be avoided in preventing prostate cancer.